Determinants of Islamic Banking Adoption in Indonesia: Attitude, Religiosity, and Financial Literacy - Samar T.M. Al Haj; Naelati Tubastuvi; Suryo Budi Santoso; Herni Justiana Astuti (Universitas Muhammadiyah Semarang, 2026)
The Islamic banking sector in Indonesia has experienced substantial growth in recent years; however, public adoption remains relatively limited. This study aims to examine the behavioral factors that shape individuals’ intention to use Islamic banking services, with particular attention to four main variables: attitude, subjective norms, religiosity, and financial literacy. Identifying these factors is important to reduce the gap between the increasing availability of Islamic financial services and their actual utilization by society. A quantitative research design was applied, involving 250 respondents from diverse demographic backgrounds across several regions in Indonesia. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate the relationships between the proposed variables. The findings indicate that attitude and financial literacy have a significant positive influence on the intention to adopt Islamic banking. Individuals who hold positive perceptions and possess sufficient financial knowledge are more likely to consider Islamic banking as an alternative financial option. On the other hand, subjective norms and religiosity do not show a significant effect on adoption intention. This suggests that personal evaluation and understanding play a more dominant role than social influence or religious considerations in shaping financial decisions. These results imply that efforts to promote Islamic banking in Indonesia should not rely solely on religious arguments. Instead, greater emphasis should be placed on effective communication strategies, financial education, and building public trust. The study provides practical insights for policymakers and Islamic financial institutions to develop more targeted programs that enhance financial literacy and promote broader financial inclusion through ethical, value-based banking systems.